Pemanfaatan Teknologi Artificial Intelligence dalam Pengembangan Kurikulum - Elva Nurbaya Sita Devi; Subiyantoro, Singgih (Kartika: Jurnal Studi Keislaman, 2026)
The rapid development of Artificial Intelligence (AI) has significantly transformed curriculum development toward more adaptive, personalized, and data-driven approaches. This study aims to analyze research trends, identify key variables, and propose future research directions related to the utilization of AI in curriculum development. This research employs a Systematic Literature Review (SLR) method based on the PRISMA guidelines. A total of 42 empirical articles published between 2020 and 2025 were retrieved from Scopus, ERIC, Semantic Scholar, and Google Scholar, and analyzed using bibliometric and thematic approaches. The results reveal three major research clusters: AI-based learning systems, curriculum intelligence design, and adaptive education models. The findings further indicate that the effectiveness of AI implementation in curriculum development is strongly influenced by mediating variables such as teacher readiness and digital pedagogy integration, and is reinforced by moderating factors including policy support and technological infrastructure readiness. In addition, ethical considerations and AI literacy emerge as critical components in designing sustainable AI-driven curricula. Overall, AI plays a strategic role in shaping innovative, inclusive, and sustainable curriculum models. This study contributes both theoretically and practically to the advancement of educational policy and technology-based curriculum design in the digital era